Life and labour of the people in London. Assisted by J. Argyle, G.E. Arkell, H. Hardy [a.o.] (MacMillan)
With graphs, indices, maps and tabs. Final volume: Notes on social influences and conclusion. 1st series: Poverty. Tome. 2-3